Diversidad de parasitoides primarios y secundarios del pulgón Myzus persicae (Hemiptera, Aphididae) en el duraznero Prunus persica (Rosales, Rosaceae) en la provincia de Mendoza, Argentina - Mazzitelli, Emilia; Aquino, Daniel A.; Gallardo, Fabiana Edith; Reche, Vanina Anadina; Ricci, Elisabet Mónica (Museu de Ciències Naturals de Barcelona, 2019)
Diversity of primary and secondary parasitoids of the aphid Myzus persicae (Hemiptera, Aphididae) in peach Punus persica (Rosales, Rosaceae) in the province of Mendoza, Argentina. Mendoza is the highest stone fruit producer and the main industrial peach producer for Argentina. Myzus persicae, known as the green peach aphid or the peach–potato aphid, is one of the main pests that affect this crop. Hymenoptera parasitoids of the Braconidae family stand out as one of the most efficient groups of natural enemies of this pest. The objectives of this study were to determine the natural parasitoidism of this peach aphid and to know the diversity of parasitoids associated with this pest. During the years 2015/2016, weekly collections were made from September to December of shoots with aphids that might or might not show signs of parasitoidism. The percentage of parasitoidism and the frequency and relative abundance of the parasitoids were calculated. The percentage of average parasitoidism per shoot was close to 20 %. About the peach–M. persicae association nine species of primary parasitoids and four species of secondary parasitoids were recorded. Aphidius colemani was the dominant species within the primary parasitoids.